2016
DOI: 10.1111/dote.12491
|View full text |Cite
|
Sign up to set email alerts
|

Complications of botulinum toxin injections for treatment of esophageal motility disorders†

Abstract: In achalasia and spastic esophageal motility disorders, botulinum toxin (botox) injection is considered an effective and low-risk procedure for short-term symptom relief. It is mainly offered to medically high-risk patients. However, no analysis of risks of botox injections has been performed. To determine the incidence and risk factors of procedure-related complications after esophageal botox injections, we analyzed the records of all patients undergoing botox injection therapy for esophageal motility disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
26
1
Order By: Relevance
“…15 As the literature is scarce on the subject, with only one ran- mediastinitis must be known by the physician and agreed by the patient before starting with this therapy. 16 Our randomized double-blind sham-controlled study yielded results somewhat different from the study reported by Vanuytsel et al 14 .…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…15 As the literature is scarce on the subject, with only one ran- mediastinitis must be known by the physician and agreed by the patient before starting with this therapy. 16 Our randomized double-blind sham-controlled study yielded results somewhat different from the study reported by Vanuytsel et al 14 .…”
Section: Discussioncontrasting
confidence: 73%
“…It was decided to perform a sham procedure in the control group (no injection) rather than saline injection because of a hypothetical infectious risk of substrate injection in the esophageal wall. Although no significant complication occurred in this series of patients, either after one or two injections of botulinum toxin, we believe that the risks of side effects (such as chest pain or heartburn), and the possibility of severe complication such as acute mediastinitis must be known by the physician and agreed by the patient before starting with this therapy …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…No ulceration, perforation, pneumothorax, or abscess were reported. Deaths is reported from acute mediastinitis following BT injection into body …”
Section: Methodsmentioning
confidence: 99%